Distal-less induces elemental color patterns in Junonia butterfly wings. Issue 1 (December 2016) - Dhungel, Bidur; Ohno, Yoshikazu; Matayoshi, Rie; Iwasaki, Mayo; Taira, Wataru; Adhikari, Kiran; Gurung, Raj; Otaki, Joji
Abstract Background The border ocellus, or eyespot, is a conspicuous color pattern element in butterfly wings. For two decades, it has been hypothesized that transcription factors such as Distal-less (Dll) are responsible for eyespot pattern development in butterfly wings, based on their expression in the prospective eyespots. In particular, it has been suggested that Dll is a determinant for eyespot size. However, functional evidence for this hypothesis has remained incomplete, due to technical difficulties. Results Here, we show that ectopically expressed Dll induces ectopic elemental color patterns in the adult wings of the blue pansy butterfly, Junonia orithya (Lepidoptera, Nymphalidae). Using baculovirus-mediated gene transfer, we misexpressed Dll protein fused with green fluorescent protein (GFP) in pupal wings, resulting in ectopic color patterns, but not the formation of intact eyespots. Induced changes included clusters of black and orange scales (a basic feature of eyespot patterns), black and gray scales, and inhibition of cover scale development. In contrast, ectopic expression of GFP alone did not induce any color pattern changes using the same baculovirus-mediated gene transfer system. Conclusions These results suggest that Dll plays an instructive role in the development of color pattern elements in butterfly wings, although Dll alone may not be sufficient to induce a complete eyespot. This study thus experimentally supports the hypothesis of Dll function in eyespot development.